SHAPING FOREIGN LANGUAGE EDUCATION IN EUROPE TOGETHER: THE EUROPEAN UNION AND THE COUNCIL OF EUROPE - Norica Felicia BUCUR (Challenges of the Knowledge Society)
At present, in many EU countries, students have the possibility to study two foreign languages along their school years and, in addition to that, adults are encouraged to start or continue foreign language learning, as the ability to communicate in a foreign language gives them the chance to come into contact with the cultural values of other peoples, develop their personalities and create wider opportunities for social integration, beneficial to the individual and profitable for the community. This paper attempts to depict the origins and the evolution of the current reality and explain the role played by the European Union and the Council of Europe in setting the trend in this particular field. Using the documentary method of research, this paper aims at providing a diachronic perspective on the events and documents that initiated and laid the foundations for foreign language education not only in the European Union, but also in Europe, at large. Moreover, by critically analysing the recent past related to foreign language education in this region, our paper might offer a useful key to better understanding the present and possibly might help raise greater awareness of the importance of foreign language skills in today’s globalized society.